KORELASI ASUPAN ZAT GIZI MAKRO, ZAT GIZI MIKRO dan AKTIFITAS FISIK dengan OBESITAS pada MAHASISWA POLTEKKES KEMENKES GORONTALO - GOI, MISRAWATIE (JURNAL HEALTH AND SPORT, 2012)
The results showed that energy intake variables are the dominant variables associated with obesity after controlled by the Cr intake, fiber intake and physical activity. Energy intake derived from the accumulation of macro-nutrient intake (carbohydrates, fats and proteins intake). Any reduction in 1 g Cr Intake, the Body Mass Index (BMI) value will rise by 0.01 kg/m2 after controlled by energy intake and physical activity variables. Any decline in physical activity score of 1 point, the BMI value will rise by 1.25 kg/m2 after controlled by the energy intake and Cr intake variables. Recommendations resulting from this research is obese people should pay attention to the balance of nutrient intake and physical activity. Needed to do research to determine the content of micronutrient chromium in food in Indonesia and determine the recommended dietary allowance rate of micronutrient chromium intake per age group.